2002
DOI: 10.4049/jimmunol.169.8.4183
|View full text |Cite
|
Sign up to set email alerts
|

Generation Ex Vivo of TGF-β-Producing Regulatory T Cells from CD4+CD25− Precursors

Abstract: Previously we reported that TGF-β has an important role in the generation and expansion of human “professional” CD4+CD25+ regulatory T cells in the periphery that have a cytokine-independent mechanism of action. In this study we used low-dose staphylococcal enterotoxin to induce T cell-dependent Ab production. We report that TGF-β induces activated CD4+CD25− T cells to become Th3 suppressor cells. While stimulating CD4+ cells with TGF-β modestly increased expression of CD25 and intracellular CTLA-4 in primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
316
2
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 411 publications
(343 citation statements)
references
References 32 publications
20
316
2
2
Order By: Relevance
“…These results may be explained by the observation that TGF-b at higher concentrations generates and expands induced Treg in ex vivo cell cultures [39]. Thus, we propose that external TGF-b supplemented in our 5-day cell cultures may induce Treg arising from CD4 1 CD25 À T cells.…”
Section: Discussionmentioning
confidence: 72%
“…These results may be explained by the observation that TGF-b at higher concentrations generates and expands induced Treg in ex vivo cell cultures [39]. Thus, we propose that external TGF-b supplemented in our 5-day cell cultures may induce Treg arising from CD4 1 CD25 À T cells.…”
Section: Discussionmentioning
confidence: 72%
“…We reported previously that TCR stimulation of CD4 ϩ cells with TGF-␤ enhances expression of CD25, CD122, CTLA-4, and GITR (8,16,19,20). Fig.…”
Section: Exogenous Il-2 Enhances the Numbers Of Cd4 ϩ Foxp3 ϩ Cells Tmentioning
confidence: 72%
“…Studies have reported that TGF-has the ability to induce CD4 + CD25 -cells to become CD4 + CD25 + Tregs in vitro [52,53], and TGF-can induce FoxP3 expression in iTregs [54,55]. Additionally, other studies have clearly demonstrated that the suppressive capacity of FoxP3 + Tregs in vivo is via a TGF--dependent mechanism [56,57].…”
Section: Transforming Growth Factor-mentioning
confidence: 99%